A Flow Cytometry‐Based Assay for High‐Throughput Detection and Quantification of Neutrophil Extracellular Traps in Mixed Cell Populations. Issue 3 (14th December 2018) - Zharkova, Olga; Tay, Sen Hee; Lee, Hui Yin; Shubhita, Tripathi; Ong, Wei Yee; Lateef, Aisha; MacAry, Paul Anthony; Lim, Lina Hsiu Kim; Connolly, John Edward; Fairhurst, Anna‐Marie
Abstract: Neutrophil extracellular traps (NETs) are web‐like structures composed of decondensed chromatin and antimicrobial proteins that are released into the extracellular space during microbial infections. This active cell death program is known as NETosis. To date, florescence microscopy is the widely accepted method for visualization and quantification of NETs. However, this method is subjective, time consuming and yields low numbers of analyzed polymorphonuclear cells (PMNs) per sample. Increasing interest has emerged on the identification of NETs using flow cytometry techniques. However, flow cytometry analysis of NETs requires particular precautions for sample preparation to obtain reproducible data. Herein, we describe a flow cytometry‐based assay for high‐throughput detection and quantification of NETosis in mixed cell populations. We used fluorescent‐labeled antibodies against cell markers on PMNs together with a combination of nucleic acid stains to measure NETosis in whole blood (WB) and purified PMNs. Using plasma membrane‐impermeable DNA‐binding dye, SYTOX Orange (SO), we found that cell‐appendant DNA of NETting PMNs were positive for SO and DAPI. The combination of optimally diluted antibody and nucleic acid dyes required no washing and yielded low background fluorescence. Significant correlations were found for NETosis from WB and purified PMNs. We then validated the assay by comparing with time‐lapse live cell fluorescence microscopy and determined very good intraassay and interassay variances. The assay was then applied to a disease associated with NETosis, systemic lupus erythematosus (SLE). We examined PMA‐induced NETosis in peripheral PMNs from SLE patients and controls and in bone marrow PMNs from multiple murine models. In summary, this assay is observer‐independent and allows for rapid assessment of a large number of PMNs per sample. Use of this assay does not require sophisticated microscopic equipment like imaging flow cytometers and may be a starting point to analyze extracellular trap formation from immune cells other than PMNs. © 2018 The Authors. Cytometry Part A published by Wiley Periodicals, Inc. on behalf of International Society for Advancement of Cytometry. Abstract :